Prevalensi serta Analisis Faktor Risiko Chronic Ankle Instability pada Mahasiswa dengan Riwayat Ankle sprain - Donal Syafrianto; Umar Umar; Afriwardi Afriwardi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Ankle sprain is one of the most common musculoskeletal injuries in sports and frequently progresses to Chronic Ankle Instability (CAI). This condition is characterized by recurrent episodes of ankle giving way, neuromuscular control deficits, and an increased risk of recurrent injury. This study aimed to determine the prevalence of CAI among university students with a history of ankle sprain using the Cumberland Ankle Instability Tool (CAIT) and to analyze the association between several risk factors and the occurrence of CAI. This study employed a cross-sectional observational design. The sample consisted of 50 students with a history of ankle sprain. Data were collected using a demographic questionnaire and the CAIT instrument. Descriptive statistics were used to determine CAI prevalence, and Chi-square analysis was applied to examine the association between risk factors and CAI. CAI was defined as a CAIT score ≤24. The findings showed that 72% of participants were classified as having CAI, while 28% were categorized as non-CAI. Statistical analysis revealed that recurrent ankle sprain was significantly associated with CAI (p = 0.008). In contrast, sex and athletic participation were not significantly associated with CAI (p > 0.05). The prevalence of CAI among students with a history of ankle sprain is relatively high. Recurrent ankle sprain appears to be the most significant risk factor contributing to CAI. These findings highlight the importance of sensorimotor and neuromuscular rehabilitation programs in physiotherapy practice to prevent the development of CAI.